ENVIRONMENTAL MANAGEMENT: PROACTIVE LEGISLATION FOR MUNICIPAL SOLID WASTE - Alessandra F. N. Pereira; Manfred Fehr (Sociedade & Natureza)
The environmental question is of complex nature. It involves knowledge of diverse subjects and makes possible the accomplishment of studies under the optics of different specialties. The philosopher Heller apud Carvalho (2001) contents that the world-wide civilization is in crisis, understands that the solution of the most serious problems is urgent, lest social and political chaos or even human self-destruction will result.Environmental Law is a science that appeared at a historical moment designated by the crisis. This science has been appraised as being a set of principles, norms and rules that have the objective of protecting the environment, maintain the ecological balance, conserve cultural assets and contribute to harmonic development and social justice. For the application of this concept, administrative and legal measures are used beyond repairing the actual damages to the environment and ecosystems (CARVALHO, 2001).The law itself is one of the tools used by the Science of Environmental Law. To command the social and cultural life in an effective process of adjustment in the light of the evolution of society is, in ample direction, the dynamics of the law. It can be observed that it also expresses the necessity of living beings to share one determined space of time and place, without the need for foreign orders devoid of adaptations.